(untitled) (mathematica didactica, 2019)
In this article, a possible framework for the cooperation of different didactics is presented. In addition, the potential didactic topics for such a scientific collaboration are explained by means of a structuring analysis of current German handbooks and conference proceedings using the example of mathematics didactics and physics didactics. The topics presented in this article can form a basis for further so-called subject-didactics-connecting projects.